Two successful insertions of peripherally inserted central catheters in a patient with persistent left superior vena cava: A case report. Issue 38 (September 2019) - Kang, Junren; Liu, Bing; Sun, Wenyan
Abstract: Rationale: Peripherally inserted central catheters (PICC), normally located at the lower 1/3rd of the superior vena cava (SVC) and cavo-atrial junction, are commonly used in cancer patients. Persistent left superior vena cava (PLSVC) is a vascular anomaly, in patients with which seldom research was reported about PICC implanted. After obtaining written informed consent, we present a case where two successful insertions of PICC were performed in a 50-year-old female patient with PLSVC and right SVC. Patients concerns: The patient had ovarian cancer and was admitted for chemotherapy using PICC. Diagnoses: Ovarian cancer and PLSVC. Interventions and Outcomes: Following insertion of PICC in PLSVC, thrombosis developed. PICC was removed after routine anticoagulation therapy. Owing to tumor recurrence, a second PICC was inserted in the right SVC without any complications. Lessons: PICC insertion in PLSVC for chemotherapy may be associated with an increased risk of deep venous thrombosis of the upper extremity. A right catheter insertion in patient with PLSVC was preferred.